Strong displayed passion and preparedness of broadcaster in live streaming e-commerce increases consumers' neural engagement - Yu, Xiaoyu; Li, Yajie; Zhu, Kexin; Wang, Wenhao; Wen, Wen (Frontiers in Psychology, 2022)
Live streaming shopping, which consumers could purchase products in real time videos, is booming in e-commerce context especially under COVID-19 threats. The success of live streaming e-commerce largely relies on to what extent the broadcaster could get consumer engaged in live streaming. Thus, the antecedents of consumer engagement are important to figure out. Drawing on literature from consumer engagement and neuroscience, this study used electroencephalography based inter-subject correlation to explore how live streaming videos influenced consumer neural engagement while they were watching real-life live streaming videos. We used the framework of entrepreneurial passion literature, displayed passion and preparedness of broadcaster, to predict the customer engagement in such setting. We found significant EEG-ISC for strong displayed passion while the effects of preparedness were partially significant on the first, second and summed components of ISC-EEG. And the conjoint effects of these two factors were partially significant on the first and summed components of ISC-EEG. As for the brain function, strong displayed passion and preparedness could activate the left and right prefrontal regions. These findings specified what is the factor to influence consumer engagement in live streaming e-commerce setting. And they also provide a scientific approach to improve broadcaster performance by testing EEG-ISC during rehearsal.